1989
DOI: 10.1002/bdd.2510100405
|View full text |Cite
|
Sign up to set email alerts
|

Buffering the stomach content enhances the absorption of diflunisal in man

Abstract: Diflunisal, a lipophilic salicylate, is absorbed more slowly in healthy volunteers than aspirin. In this paper we report on attempts to influence diflunisal absorption by buffering the gastric milieu. Sodium bicarbonate given together and 30 min after diflunisal tablets significantly (p less than 0.05) shortened the time to reach peak plasma concentration (tmax greater than 15 per cent), raised maximum plasma concentration slightly (Cmax 6 per cent) and increased the area under the plasma concentration-time cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For quantification of acteylsalicylic acid (ASA) and salicylic acid (SA) an isocratic high performance liquid chromatographic ultraviolet-method was used, according to Amick and Mason [29], Nieder et al [30], see also [31]. The detection limits for ASA and SA were found to be less than 1 gg/ml.…”
Section: Materials and Methods For Determination Of Blood Plasma Levelsmentioning
confidence: 99%
“…For quantification of acteylsalicylic acid (ASA) and salicylic acid (SA) an isocratic high performance liquid chromatographic ultraviolet-method was used, according to Amick and Mason [29], Nieder et al [30], see also [31]. The detection limits for ASA and SA were found to be less than 1 gg/ml.…”
Section: Materials and Methods For Determination Of Blood Plasma Levelsmentioning
confidence: 99%
“…Based on PubChem, the solubility of diflunisal is 14.5 mg/L at neutral or acidic pH, which is impractical to be formulated into a solution for oral desensitization. One study has shown that buffering gastric pH toward neutral using sodium bicarbonate has enhanced the absorption of diflunisal in addition to its bioavailability [10]. Hence, it was extrapolated that the solubility of diflunisal may be improved with the use of sodium bicarbonate as the solvent.…”
Section: Discussionmentioning
confidence: 99%
“…14  Reduced gastrointestinal irritation: By buffering the stomach acid, effervescent formulations might lessen the gastrointestinal irritation brought on by some drugs. 15  Improved portability: When compared to liquid dose forms, effervescent tablets are easier to store and transport because of their compact form. 10  Increased palatability: Flavouring agents are frequently used in the formulation of effervescent tablets to enhance their flavour and increase patient acceptability.…”
Section: Pros Of Effervescent Tabletsmentioning
confidence: 99%